HUBUNGAN GIZI KERJA, TEKNOLOGI YANG DIGUNAKAN DAN MOTIVASI KERJA DENGAN PRODUKTIVITAS KERJA PEMANEN KELAPA SAWIT PT. SINERGI AGRO INDUSTRI KECAMATAN SANDARAN KABUPATEN KUTAI TIMUR - Suwignyo Suwignyo; Ayusma Saputri (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2018)
The important problem faced by the leaders of a company is how to improve employee productivity, so it can support the achievement of goals. The purpose of this study to determine the relationship work nutrition, technology used and work motivation with work productivity of palm oil harvester PT. Synergy Agro Industry.Type of research used descriptive correlational with cross sectional study design. Sample in this research worker of palm oil harvester PT. Synergy Agro Industry amounted to 59 respondents, with sampling technique is purposive sampling. Data analysis using chi square.The results showed that there is no correlation working nutritional with the productivity of oil palm harvester PT. Synergy of Agro Industry (with p value = 0,114 > ? = 0,05). There is a technological correlation used with the productivity of PT palm oil harvesters Agro Industry Synergy (with p value = 0,001 < ? = 0,05). There is a working motivation correlation with the productivity of oil palm harvester PT. Agro Industry Synergy (with p value = 0,007 < ? = 0,05).The conclusion in this research is technology used and work motivation are factors related to work productivity. Recommended PT. Synergy Agro Industries provide motivation to workers by increasing the number of incentives per day if the target is reached. Keywords: Working Nutrition, Technology, Motivation, Work Productivity